Sea Sickness in Naval Personnel - Malek, MA; Maruf, AA; Hossain, MM (Journal of Armed Forces Medical College, Bangladesh, 2010)
Seasickness can be a debilitating condition and can be dangerous if the naval personnel appointed in operational or key appointment in the ship during operation. The objective of this descriptive study was to report and evaluate the incidence, severity and effects of seasickness among naval personnel of Khulna Naval Base. The study was conducted over a period of 18 months. This study included 1293 healthy male sailors and aged ranges between 20 to 45 years. Data included sailor's demographics, duration at sea, types of symptoms, severity of seasickness, incidence of seasickness in relation to exposure, and sea condition. Total 785 (60.71%) sailors stayed less then 7 days, 311 (24.06%) from 7 to 14 days and 197 (15.23%) stayed more than 14 days. Total 523 (40.44%) sailors experienced seasickness; those were dizziness (18.32%), fatigue (17.09%), vertigo (11.36%), epigastric discomfort (9.74%), nausea (17.40%) and vomiting (6.57%). Majority were minor inconvenience, self limiting and did not require rest (78.78%).Excuse from duty for 24 hours was required in 101 (19.31%) cases and excused from duty for whole sea period in 10 (1.91%) cases. Incidence of seasickness observed in first exposure in 275 (52.59%) cases, after less than 10 exposure in 138 (26.39%) cases, after more than 10 exposure in 69 (13.18%) cases and always in 41 (7.84%) cases. Sailors had seasickness in calm sea (3.82%), in moderate sea (24.28%) and in rough sea (71.70%). No sailor required evacuation from sea to land for seasickness. Seasickness is troublesome for sailors, but majority of the symptoms were minor inconvenience and self-limiting without very few exceptions. For better confirmation and future prospect, study may be conducted in a larger aspect including both sexes. Key words: Seasickness, sailor, naval person.